Road to the Welfare State - Committee on Plan Projects Planning Commission (Committee on Plan Projects Planning Commission Government of India, 1955)
Road to the Welfare State presents a foundational vision of India’s transition toward a welfare-oriented society through community-driven development. Issued by the Community Projects Administration, the document traces the historical context from colonial exploitation to post-independence challenges and situates the First Five-Year Plan as a response to economic scarcity and social inequality. Central to the welfare strategy is the Community Development Programme, which emphasizes local participation, integrated rural development, and democratic decentralization through Panchayats and the National Extension Service. Complementing this vision, the accompanying analysis of trades, professions, and services provides an empirical snapshot of workforce distribution, illustrating the diverse economic base supporting community life. Together, the documents underscore the belief that sustainable welfare emerges not merely from state provision but from collective effort, self-help, and active citizen participation in nation-building.
The Community Projects Administration (Planning Commission) Government of India
Keywords: Road to the Welfare State; Community Development Programme; Community Projects Administration; Welfare State Philosophy; First Five-Year Plan Context; National Extension Service; Village Level Workers; Panchayati Raj Framework; Grassroots Participation Model; Community Self-Help Strategy; Rural Employment Structure; Trades and Services Distribution